15-Lipoxygenase-1 Is Involved in the Effects of Atorvastatin on Endothelial Dysfunction. (10th August 2016) - Zhang, Peng; Xing, Xin; Hu, Chunxiao; Yu, Hui; Dong, Qian; Chang, Guanglei; Qin, Shu; Liu, Jian; Zhang, Dongying
Abstract : Statins exert pleiotropic effects on endothelial cells in addition to lowering cholesterol. 15-Lipoxygenase-1 (ALOX15) has been implicated in vascular inflammation and disease. The relationship between atorvastatin and ALOX15 was investigated using a rat carotid artery balloon-injury model. Hematoxylin and eosin (HE) staining showed that ALOX15 overexpression increased the thickness of the intima-media (IMT). Immunohistochemistry and western blotting showed that atorvastatin increased the expression of cellular adhesion molecules (CAMs) but decreased the expression of endothelial nitric oxide synthase (eNOS); these effects of atorvastatin were blocked by ALOX15 overexpression. In human umbilical venous endothelial cells (HUVECs), silencing of ALOX15 enhanced the effects of atorvastatin on endothelial function. Expression levels of CAMs and Akt/eNOS/NO under oxidized low-density lipoprotein (ox-LDL) stimulation were modulated by ALOX15 inhibitor and ALOX15 small interfering RNA (siRNA). Atorvastatin abolished the activation of nuclear factor-kappa B (NF- κ B) induced by ox-LDL. Exposure to ox-LDL induced upregulation of ALOX15 in HUVECs, but this effect was partially abolished by atorvastatin or the NF- κ B inhibitor pyrrolidine dithiocarbamate (PDTC). These results demonstrate that regulation of ALOX15 expression might be involved in the effects of atorvastatin on endothelial dysfunction.